DEVELOPMENT OF E-MODULES BASED ON STAD TYPE COOPERATIVE LEARNING USING RACING GAMES ON SEQUENCES AND SERIES - Winda Febryanti; Sutrisni Andayani; Ira Vahlia (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to develop an e-module based on cooperative learning of the STAD type assisted by racing games on the material of sequences and series. The background of this study is the lack of teaching materials used by students in learning, the available books are also different from the current curriculum used so they are rarely used. The learning is also still conventional so that students feel monotonous and have difficulty understanding the material. The research method used is the ADDIE model including analysis, design, development, implementation, and evaluation. At the analysis stage, interviews were conducted with educators and questionnaires were given to students to identify problems and needs, the design stage designed the e-module, the development stage conducted validation tests of materials and media as well as practicality tests to 15 students, and the evaluation stage was carried out at each stage to improve the e-module. The average result of material validation was 81% with a very valid category. The average result of media validation was 89% with a very valid category. The results of the practicality test got an average of 89.87% with a very practical category. This development provides opportunities for educators to integrate technology in cooperative learning in the learning process. Keywords: Sequences and Series; E-module; Racing Games; STAD-Type Cooperative Learning; Development